(untitled) (Research, Society and Development, 2024)
Background: Depression represents an important health problem and has a prevalence of 9.7% in Brazil. As for the Burden of Disease, depression ranks as the 3rd cause of Years Lived with Disability (YLD) in the world and the 4th cause in Brazil. Objective: to analyze the association between depressive symptoms and sociodemographic factors, self-perceived health, alcohol use, and violence in a sample of Primary Health Care (PHC) users, Municipality of Belo Horizonte, State of Minas Gerais, Brazil. Methods: A total of 1,125 PHC patients from Belo Horizonte participated in the study (16 years or older). A filter was applied to 1,105 patients over 18 years of age. Depressive symptoms (based on DSM IV) and sociodemographic factors, self-perceived health, alcohol use, and exposure to violence were evaluated. Results: The prevalence of depressive syndrome was 31.4%. The associated factors identified were female, OR 3.3 (1.7-6.5); low income, OR 2.6 (1.1-6.3); not working in a paid activity, OR 1.9 (1.1-3.7); negative self-perceived health, OR 2.3 (1.2-4.2); positive CAGE, OR 3.3 (1.5-7.1); binge drinking, OR 2.2 (1.2-4.3); alcoholic amnesia, OR 2.2 (1.0-4.9) and murdered family member, OR 2.2 (1.1-4.2). Conclusion: The prevalence of depressive symptoms is similar to that of other studies, and the factors associated with females, low income, not working in a paid activity, negative self-perceived health, alcohol abuse, and a murdered family member were identified.